2010
DOI: 10.1016/j.ijid.2010.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in CD4+CD25+FoxP3+ Treg cells after pulmonary resection in the treatment of cavity multidrug-resistant tuberculosis

Abstract: Circulating T(reg) cells are increased in proportion in patients with cavity MDR-TB and decreased after surgery. Infection with M. tuberculosis may induce T(reg) cell-surface molecular changes with increased numbers of cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…It has been previously reported that patients with TB have a high proportion of circulating T reg cells of the CD4 + CD25 + FOXP3 + phenotype compared with patients with LTBI or uninfected controls (7,8). A previous study by our group revealed that the elevated numbers of CD4 + CD25 + FOXP3 + cells observed in MDR-TB were found to decrease following removal of the M. tuberculosis burden by pulmonary resection (9), which demonstrated that the increase in FOXP3 + T reg cells is a potential mechanism by which M. tuberculosis evades immune eradication. In individuals with tuberculosis, these cells have been observed to suppress the T-cell response to mycobacterial antigens, whereas the CD4 + CD25 + FOXP3 + cells from non-healthy individuals do not suppress the secretion of IFN-γ induced by protective mycobacterial antigens (8,23).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…It has been previously reported that patients with TB have a high proportion of circulating T reg cells of the CD4 + CD25 + FOXP3 + phenotype compared with patients with LTBI or uninfected controls (7,8). A previous study by our group revealed that the elevated numbers of CD4 + CD25 + FOXP3 + cells observed in MDR-TB were found to decrease following removal of the M. tuberculosis burden by pulmonary resection (9), which demonstrated that the increase in FOXP3 + T reg cells is a potential mechanism by which M. tuberculosis evades immune eradication. In individuals with tuberculosis, these cells have been observed to suppress the T-cell response to mycobacterial antigens, whereas the CD4 + CD25 + FOXP3 + cells from non-healthy individuals do not suppress the secretion of IFN-γ induced by protective mycobacterial antigens (8,23).…”
Section: Discussionmentioning
confidence: 73%
“…Several previous studies have found that the number of FOXP3 + T reg cells is increased in patients with active TB and are expanded at sites of active disease, where containment of inflammation and immune-mediated pathology is required most (7,8). A previous study by our group demonstrated that elevated levels of FOXP3 + T reg cells decreased following pulmonary resection in patients with pulmonary multiplicitous drug resistant tuberculosis (MDR-TB) (9). This suggested that FOXP3 + cells may be essential during TB development; however, the mechanism underlying the increased levels of FOXP3 + cells in active TB patients remains to be elucidated.…”
Section: Introductionmentioning
confidence: 98%
“…In active TB, the immunological balance fails, inflammation increases and larger numbers of Treg cells are recruited to the site of infection, indicated by higher frequencies of circulating Treg cells [18,19,28,29,36]. Supporting this finding, infected macaques show decreasing numbers of circulating Treg cells during the first weeks following infection, as these are recruited to the lung.…”
Section: Discussionmentioning
confidence: 76%
“…In TB, the numbers of circulating Treg cells decrease after resection of pulmonary cavities [36]. Therefore, Treg cells or their surrogate markers (TGF-b1 and IL-10) merit further investigation for the monitoring of TB treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…peripheral T-regulatory cells, exhaustion T cells) and inflammatory proteins (i.e. vascular endothelial growth factor, interferon-γ-inducible protein 10) in the course of treatment was also described [96,97,98]. Biomarkers or compound markers consisting of blood markers, radiological assessment by chest X-ray, CT or positron emission tomography-CT, and clinical scores could eventually help to subsequently individualize the duration of therapy for patients affected by chronic respiratory infections [14,99,100].…”
Section: Future Perspective: Personalized Medicine To Improve Clinicamentioning
confidence: 99%